Philanthropic Giving and Volunteering Among Religious Disaffiliates - Taggart, Gabel (Journal for the scientific study of religion, 2024)
Increasing numbers of religious disaffiliates in the United States is a notable demographic shift with deep implications for the money donated in the philanthropic sector. We seek to understand this change in more detail by analyzing philanthropic giving and volunteering patterns among religious disaffiliates using data from the General Social Survey. This article identifies that people who were religious at age 16 but leave later in life gave less to charitable causes, gave less often, and were less likely to have volunteered recently than their consistently religious counterparts. This article initiates the study of philanthropy specifically among religious disaffiliates, and so we conclude by discussing areas for further research that could further address fundamental questions about religious disaffiliates and their philanthropic behavior. By examining religious disaffiliates, this article adds nuance to more common comparisons of giving and volunteering across religious and nonreligious people. With changing religiosity in the United States, understanding these philanthropic changes is important for the future of both secular and religious nonprofits that rely on these donations for funding.